2022
DOI: 10.1038/s41598-022-15840-0
|View full text |Cite
|
Sign up to set email alerts
|

IκBζ regulates the development of nonalcoholic fatty liver disease through the attenuation of hepatic steatosis in mice

Abstract: IκBζ is a transcriptional regulator that augments inflammatory responses from the Toll-like receptor or interleukin signaling. These innate immune responses contribute to the progression of nonalcoholic fatty liver disease (NAFLD); however, the role of IκBζ in the pathogenesis of NAFLD remains elusive. We investigated whether IκBζ was involved in the progression of NAFLD in mice. We generated hepatocyte-specific IκBζ-deficient mice (Alb-Cre; Nfkbizfl/fl) by crossing Nfkbizfl/fl mice with Alb-Cre transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…NFKBIZ rs645781 and NFKBIZ rs677011 have been closely associated with the risk of invasive pneumococcal disease (IPD) ( 152 ). Lipin1 coordinates liver metabolism, and IκBζ ameliorates fatty liver by downregulating Lipin1 ( 153 ). The NFKBIZ rs3217713 II genotype has been associated with a higher risk of death among COVID-19 patients with severe infection in the ICU ( 154 ).…”
Section: Diseases Related To Iκbζ In the Context Of Inflammationmentioning
confidence: 99%
“…NFKBIZ rs645781 and NFKBIZ rs677011 have been closely associated with the risk of invasive pneumococcal disease (IPD) ( 152 ). Lipin1 coordinates liver metabolism, and IκBζ ameliorates fatty liver by downregulating Lipin1 ( 153 ). The NFKBIZ rs3217713 II genotype has been associated with a higher risk of death among COVID-19 patients with severe infection in the ICU ( 154 ).…”
Section: Diseases Related To Iκbζ In the Context Of Inflammationmentioning
confidence: 99%
“…IκBζ-dependent genes include IL-6 and lipocalin-2 that contribute to controlling acute hepatitis and bacterial infection [ 56 ]. Hepatic IκBζ regulates the factors related to triglyceride metabolism, which attenuates the progression of non-alcoholic fatty liver disease in mice [ 57 ]. Galectin-1 can downregulate IκBζ in the primary cultures of decidua cells, which is related with downregulation of the inflammatory response and the abundance of anti-inflammatory molecules during gestation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relative research of bladder cancer showed NFKBIZ exerted an antitumoral effect by modulating PTEN/PI3K/Akt signaling pathway [ 11 ]. Previous researches have also indicated the intimate correlation between dysregulated expression of NFKBIZ and liver diseases such as acute hepatitis, nonalcoholic fatty liver disease and HBV- related HCC [ 12 , 13 ]. Mechanistically, NFKBIZ downregulation can suppress the expression of IL-6 (a hepatoprotective cytokine) and resulted in restricted inhibition of hepatitis; NFKBIZ can also regulate triglyceride metabolism to attenuate the progression of nonalcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%